2020
DOI: 10.1038/s41598-020-63999-1
|View full text |Cite
|
Sign up to set email alerts
|

Analogies can speed up the motor learning process

Abstract: Analogies have been shown to improve motor learning in various tasks and settings. in this study we tested whether applying analogies can shorten the motor learning process and induce insight and skill improvement in tasks that usually demand many hours of practice. Kinematic measures were used to quantify participant's skill and learning dynamics. For this purpose, we used a drawing task, in which subjects drew lines to connect dots, and a mirror game, in which subjects tracked a moving stimulus. After establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The finding of this study revealed that students' conceptual understanding of some selected contents of electricity and magnetism such as the concept of charge, coulomb's force, electric field and its strength from a point charge, electric potential and electric potential energy, current, voltage, resistance, combination of resistors, electromotive force, magnetic field and the associated forces include in high school physics enhanced when simulated analogies were used in support of group discussion method. The result of finding was in accordance with the study carried out on the use of analogies as it helps to increase learners mental process (Jonane, 2015;Zacks & Friedman, 2020). The simulated analogical reasoning scaffold by group discussion method help students to structure and integrate new information with past experiences so that they can retrieve from memory so as to link with other concepts be learnt in another context.…”
Section: Resultssupporting
confidence: 82%
“…The finding of this study revealed that students' conceptual understanding of some selected contents of electricity and magnetism such as the concept of charge, coulomb's force, electric field and its strength from a point charge, electric potential and electric potential energy, current, voltage, resistance, combination of resistors, electromotive force, magnetic field and the associated forces include in high school physics enhanced when simulated analogies were used in support of group discussion method. The result of finding was in accordance with the study carried out on the use of analogies as it helps to increase learners mental process (Jonane, 2015;Zacks & Friedman, 2020). The simulated analogical reasoning scaffold by group discussion method help students to structure and integrate new information with past experiences so that they can retrieve from memory so as to link with other concepts be learnt in another context.…”
Section: Resultssupporting
confidence: 82%
“…The added value of body-based measures is even more obvious in cultures where writing systems would not be available. Body-based units may also be useful in the construction of analogies, which can facilitate reasoning (87) and the acquisition of motor skills (88). Analogies such as measuring trees or houses in terms of "lengths of a man", as done by the Kogi (89), could therefore serve as useful facilitators for learning.…”
Section: Cognitive Ease: Offloading and Analogiesmentioning
confidence: 99%
“…Se ha demostrado que el uso regular de analogías dentro de la enseñanza de las ciencias facilita procesos cognitivos como: el aprendizaje, la abstracción, el razonamiento y el recuerdo de conceptos científicos (Gentner & Hoyos, 2017;Suryanda et al, 2020). Además, permite comprender fenómenos teóricos o intangibles (Fleck & Hachet, 2016), facilita el aprendizaje de procesos motores y/o tareas rutinarias (Zacks & Friedman, 2020), proporciona la generación de nuevas ideas (Aragón Méndez, 2013;Bingham & Kahl, 2013), favorece la resolución de problemas (Mair et al, 2009;Chan et al, 2012;Keefer & Landau, 2016), el desarrollo de la imaginación (Schwarz-Plaschg, 2018), el pensamiento matemático intuitivo (Kurniawati, et al, 2022), y el pensamiento innovador (Herstatt & Kalogerakis, 2005). Recientemente, Sezer & Karatas (2022), examinaron 80 estudios publicados entre 2009 y 2020, para determinar el uso de las analogías como métodos de enseñanza de las ciencias.…”
Section: Introductionunclassified